The Influence of Sensitivity Analysis on ohe Process of Price Decision Making and Pricing of the Company - Kubjatkova Anna (SHS Web of Conferences, 2021)
Research background: An integral part of the existence of every company is the constant making of various decisions that affect the company and its surroundings on a global scale. These decisions include decisions about price, which is a key element of the company’s interaction with its surroundings. In the conditions of globalization, price is a key factor in the competition, and price decisions must be made by the company very carefully and their selection is not easy. Sensitivity analysis helps companies choose the best options and steps in the price decision making, which will ultimately affect the process of pricing. Purpose of the article: The purpose of this work is to point out the importance of sensitivity analysis as a tool for simplifying price decision making and to perform this analysis on a model example of a company. Methods: Methods of analysis and research of the issue were used in the paper. Induction and deduction methods were also used to help provide a comprehensive picture of sensitivity analysis. Findings & Value added: The result of this work is, in addition to a general overview of the sensitivity analysis in price decision making, also the specific procedure and the results of the sensitivity analysis and recommendations for the company resulting from these results. Based on the created instructions, companies can make clear pricing decisions that will be of the greatest benefit to them.